2014
DOI: 10.1371/journal.pone.0084294
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Na+/H+ Exchanger Activation Promotes Gliotransmitter Release from Reactive Hippocampal Astrocytes following Oxygen-Glucose Deprivation

Abstract: Hypoxia ischemia (HI)-related brain injury is the major cause of long-term morbidity in neonates. One characteristic hallmark of neonatal HI is the development of reactive astrogliosis in the hippocampus. However, the impact of reactive astrogliosis in hippocampal damage after neonatal HI is not fully understood. In the current study, we investigated the role of Na+/H+ exchanger isoform 1 (NHE1) protein in mouse reactive hippocampal astrocyte function in an in vitro ischemia model (oxygen/glucose deprivation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Following OGD/REOX, upregulation of GFAP expression in response to reactive astrogliosis has been reported 20 . Although, it has been proposed that GFAP overexpression could be used as specific target for neuronal repair strategies 27 its role in hippocampal damage after HI in neonates is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following OGD/REOX, upregulation of GFAP expression in response to reactive astrogliosis has been reported 20 . Although, it has been proposed that GFAP overexpression could be used as specific target for neuronal repair strategies 27 its role in hippocampal damage after HI in neonates is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…If the intended use of the astrocyte culture is to study the role of hippocampal astrocytes in inflammation it is imperative to treat the cultures with 5 mM LME for 10 d to eliminate possible microglial contamination in the astrocyte cultures starting from DIV 3. LME is a microglial cytotoxic agent that has been used extensively as a method to remove proliferating microglia 20,22 . In addition, LME-treated cultures should be subjected to a shaking protocol (300 rpm for 1 h).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of extra-synaptic glutamate is cleared by the glutamate transports GLAST and GLT-1 in astrocytes, which also express NHE1, NHE9, and likely NHE6 (Anderson and Swanson, 2000; Cahoy et al, 2008; Cengiz et al, 2014; Kondapalli et al, 2013). The transport of both glutamine and glutamate is sensitive to pH changes, thus NHE proteins, like NHE6 and NHE9, can play a role in controlling the transportation of these compounds (Gilfillan et al, 2008; Swanson et al, 1995).…”
Section: Epilepsy and Nhe6/nhe9 Mutationsmentioning
confidence: 99%
“…These acid regulatory mechanisms have been examined in different neurons of the CNS (Chesler, 2003), of which the Na + /H + exchange is the most prevalent mechanism in all neurons. It was reported that in various CNS cell cultures, NHE1 plays a dominant role in pH i regulation, including cortical neurons (Luo et al, 2005), cortical and hippocampal astrocytes (Cengiz et al, 2013;Kintner et al, 2004), as well as primary microglia (Liu et al, 2010). NHE1 is highly sensitive to pH i changes, and reduction of pH i allosterically increases its protein activity (Aronson et al, 1982).…”
Section: The Sodium/hydrogen Exchangersmentioning
confidence: 99%
“…In cultured mouse cortical astrocytes, OGD/REOX significantly stimulates NHE1 activity, leading to accumulation of intracellular Na + and Ca 2+ (Kintner et al, 2004). In mouse hippocampal astrocytes, 5 h REOX caused intracellular Na + to reach 35 mM and significantly impaired glutamate uptake (Cengiz et al, 2013). NHE1 inhibition or genetic knockdown significantly attenuated the [Na + ] i rise and cell swelling (Kintner et al, 2004), and facilitated glutamate uptake by astrocytes.…”
Section: The Sodium/hydrogen Exchangersmentioning
confidence: 99%